Genotypic diversity and acidogenicity of Streptococcus mutans in Down syndrome children. (12th September 2019) - Moreira, Maurício José Santos; Klaus, Natália Mincato; Dall'Onder, Ana Paula; Grando, Débora; Parolo, Clarissa Cavalcanti Fatturi; Faccini, Lavinia Schuler; Hashizume, Lina Naomi
Abstract: Aims: To evaluate the genotypic diversity and acidogenicity of Streptococcus mutans ( S. mutans ) and the potential association of these factors with dental caries experience in children with DS compared to non‐DS children (controls). Methods and results: Seventeen children (age 6‐12 years) with high salivary S. mutans counts (> 2.5 × 10 5 CFU/mL) were selected and divided into two groups: DS and non‐DS. Five children in each group were caries‐free, while the remainder had elevated caries experience. S. mutans isolates were obtained from each participant. The genotypic profile of the isolates was analyzed with the AP‐PCR methodology. The acidogenicity of a representative strain from each genotype of S. mutans was also evaluated. DS children had 16 different S. mutans genotypes, while the control group had 21. Twelve genotypes were present in both groups and one of them was associated with caries‐free status ( P  < .05). Although the acidogenicity of the genotypes found in DS children was significantly lower ( P  < .05) compared to controls, this fact was not associated with caries experience in both groups. Conclusions: DS children have a lower S. mutans genotypic diversity and genotypes with lower acidogenicity than those of non‐DS children. However these findings were not associated with their caries experience.